Toward Place-Based Peace Pedagogies - Munroe, Amanda (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
Following from an ecological paradigm for peace, this article promotes a focus on place as an anchor for peacelearning, deconstructing colonial notions of place and introducing place-based peace education as a strategy for planetary resilience in the face of ecological crisis. Departing from IIPE 2024’s theme, "Navigating the Tensions between tradition and modernity" and drawing on philosophical scholarship on place, the author deconstructs colonial imprints of the notions of linear time, the “atomic” or “unencumbered” self, and enclosure on current notions of place, then introduces opportunities to construct place-based peace pedagogies. Place is compared to an ecosystem, constituted by the integrity of connections among beings and as stable and resilient as the strength of the bonds between them. The article concludes with an argument for place-based pedagogies that foster connections among learners and that situate learners as neighbors: beings in relationship with each other, human neighbors, and more-than human neighbors, including plants, animals, and land. Invoking Reardon’s (2021) notion that “comprehensive peace education” is an education “for global responsibility” this article seeks to weave existing work in place-based learning into growing scholarship on an ecological paradigm for peace education.